Student engagement: concepts, development and application in Malaysian universities - Abdullah, Maria Chong; Teoh, H. C.; Roslan, Samsilah; Uli, Jegak (Mediterranean Center of Social and Educational Research, 2015)
The purpose of this article is to analyse, evaluate and synthesise the concept and development of student engagement in higher education institutions so that the possibility of application in Malaysian universities can be realised. The main discussion of this article is organised into four sections. The first section focuses on the definition of engagement and on why it is important for higher education institutions. In the second, the article describes the antecedent of the concept and its evolution over the last thirty years. The third section analyses critically the function of student engagement as a proxy, means or end in research. Finally, the article highlights the necessity, limitations, and implications of adapting student engagement to the Malaysian context. Through the overview, it is proven that student engagement is a concept well developed in theory and practice. Various studies have proven the effectiveness of student engagement in serving institutional and individual development. With this understanding of the concept of student engagement, perhaps it will widen and deepen the perception of administrators, lecturers, and the general public towards the development of higher education. Subsequently, is may increase undergraduates’ level of commitment and meet the challenge of society.